The early Palaeogene transition from thin-skinned to thick-skinned shortening in the Potosí uplift, Sierra Madre Oriental, northeastern Mexico. Issue 2 (22nd January 2021) - Williams, Stewart A.; Singleton, J. S.; Prior, M. G.; Mavor, S. P.; Cross, G. E.; Stockli, D.F.
ABSTRACT: The central Sierra Madre Oriental in Mexico developed primarily in the Late Cretaceous to early Palaeogene as a thin-skinned fold belt above a décollement hosted in Jurassic evaporite. In some regions shortening transitioned to sub-décollement structural levels, resulting in thick-skinned uplifts such as the Potosí uplift in Nuevo León. Thick-skinned deformation in the Potosí uplift involved folding of sub-décollement strata into an NNW-trending anticlinorium, cleavage development, thrust and conjugate strike-slip faulting, and extension fractures associated with barite mineralization. These structures consistently record subhorizontal shortening, directed ~52–65° in the southern uplift, ~69–72° in the northern uplift. Palaeocene to mid-Eocene zircon (U-Th)/He cooling dates record the timing of exhumation associated with thick-skinned uplift and suggest a continuation of shortening rather than a separate tectonic event. Zircon (U-Th)/He dates across the southern Potosí uplift and the Aramberri uplift, ~50 km to the south, range from ~66–53 Ma, whereas dates in the northern part of the Potosí uplift range from ~49–44 Ma. We attribute the transition to thick-skinned shortening to the mechanical strengthening of a planar décollement as rheologically weak evaporite was evacuated beneath synclinal keels of detachment folds. Along-strike differences in timing of exhumation and shortening directions may relate to differences in mechanical stratigraphy. Thicker intervals of evaporite in the northern uplift allowed thin-skinned shortening to continue while the southern uplift transitioned to thick-skinned shortening as the evaporite décollement was exhausted. As a result, stress-strain trajectories in the northern uplift refracted clockwise during continued deformation. Our findings provide new insight into the structural evolution of the Potosí uplift and may provide a framework for studying other thick-skinned uplifts in the orogen, and more generally orogenic belts that record a transition in deformation styles during progressive shortening.